NAD metabolism fuels human and mouse intestinal inflammation. Issue 10 (6th September 2017) - Gerner, Romana R; Klepsch, Victoria; Macheiner, Sophie; Arnhard, Kathrin; Adolph, Timon E; Grander, Christoph; Wieser, Verena; Pfister, Alexandra; Moser, Patrizia; Hermann-Kleiter, Natascha; Baier, Gottfried; Oberacher, Herbert; et al.
Abstract : Objective: Nicotinamide phosphoribosyltransferase (NAMPT, also referred to as pre-B cell colony-enhancing factor or visfatin) is critically required for the maintenance of cellular nicotinamide adenine dinucleotide (NAD) supply catalysing the rate-limiting step of the NAD salvage pathway . NAMPT is strongly upregulated in inflammation including IBD and counteracts an increased cellular NAD turnover mediated by NAD-depleting enzymes. These constitute an important mechanistic link between inflammatory, metabolic and transcriptional pathways and NAD metabolism. Design: We investigated the impact of NAMPT inhibition by the small-molecule inhibitor FK866 in the dextran sulfate sodium (DSS) model of colitis and the azoxymethane/DSS model of colitis-associated cancer. The impact of NAD depletion on differentiation of mouse and human primary monocytes/macrophages was studied in vitro. Finally, we tested the efficacy of FK866 compared with dexamethasone and infliximab in lamina propria mononuclear cells (LPMNC) isolated from patients with IBD. Results: FK866 ameliorated DSS-induced colitis and suppressed inflammation-associated tumorigenesis in mice. FK866 potently inhibited NAMPT activity as demonstrated by reduced mucosal NAD, resulting in reduced abundances and activities of NAD-dependent enzymes including PARP1, Sirt6 and CD38, reduced nuclear factor kappa B activation, and decreased cellular infiltration by inflammatory monocytes, macrophages and activated T cells. Remarkably, FK866 effectively supressed cytokine release from LPMNCs of patients with IBD. As FK866 was also effective in Rag1 −⁄− mice, we mechanistically linked FK866 treatment with altered monocyte/macrophage biology and skewed macrophage polarisation by reducing CD86, CD38, MHC-II and interleukin (IL)-6 and promoting CD206, Egr2 and IL-10. Conclusion: Our data emphasise the importance of NAD immunometabolism for mucosal immunity and highlight FK866-mediated NAMPT blockade as a promising therapeutic approach in acute intestinal inflammation.